Inter-counter linkage in Kuala Lumpur Stock Exchange returns - Faoziah Idris,; Tang, Tuck Cheong (Sunway University College, 2004)
This paper investigates the linkages among daily returns of the Kuala Lumpur Stock Exchange (KLSE) counters over the period 7 July 1995 to10 August 1999. It examines the dynamic causal linkages among nine counters and then quantifies the extent of their dynamic interdependencies through the application of time series econometric technique of Granger causality tests. The counters selected are mining, consumer product, finance, industrials, industrial product, properties, construction, plantations, and trading?services. The findings successfully establish the existence of inter-linkages among the nine selected counters.